Pengaruh Size, Profitability, dan Liquidity terhadap Effective Tax Rates (ETR) Bank Devisa Periode 2010 – 2014 - Amanda Nur Putri; Gunawan Gunawan (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this study is to empirically examine whether the included size, profitability, and liquidity affect the effective tax rate (ETR) in foreign exchange bank listed in Indonesia Stock Exchange. Population taken as the object of observation is 20 foreign exchange bank listed on Indonesia Stock Exchange in the period 2010-2014. Determination of the sample was made by applying purposive sampling method and obtain a sample of 13 foreign exchange bank based on certain criteria. The dependent variable is effective tax rate (ETR). The independent variables are size, Profitability, and Liquidity.The results showed that the size and profitability negative significant effect on the effective tax rate. While liquidity does not significantly influence the effective tax rate. Empirical result of this study has implication for The Big size of the bank can use tax planning to reduces effective tax rate (ETR).